The Addition of Mangrove Leaf Extract Rhizophora apiculata in White Shrimp (Litopenaeus vannamei) for Vibriosis Prevention - Nur Fadillah; Saptono Waspodo; Fariq Azhar (Journal of Aquaculture Science, 2019)
White shrimp is a brackish water commodity which is a solution to approve tiger shrimp (Penaeus monodon) which improves quality. One of the challenges in the cultivation of white shrimp is the attack of vibriosis, caused by the vibrio genus species V. parahaemolyticus. Rhizophora apiculata mangrove leaf extract with different dosages in white shrimp feed to increase vibriosis. Shrimp were given mangrove leaf extract for 40 days and were challenged for 7 days in a 40cm x 30cm x 28cm container, 20 heads/20 liter volume container. The study was conducted in 5 training, control + (Feed without extract + Infection), control- (feed without extract), P3 (0,5% + Infection), P4 (1% extract + Infection), P5 (2% extract + Infection ), the injected bacterial dose is 0.1 ml/heads density of 106 cfu/ml. The results showed that administration of mangrove leaf extract at a dose of 2% was able to maintain SR of 76,67%, increasing shrimp THC by 7,55í”106 cells/ml and DHC (hyaline cells 84,3% and granular 15,3%) which plan in the shrimp immune system. The number of bacteria and the amount of vibrio in the intestine is, 64,7í”108 cfu/ml and 16í”108 cfu/ml. Based on the results of the study, the use of mangrove leaf extract can be used in the cultivation of white shrimp as an immunostimulant because it can increase survival, THC, DHC and reduce bacteria in the intestines of white shrimp. Keywords: extracts, mangrove leaves, vibriosis, white shrimp, feed.